If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -4 = 12x + -6 Reorder the terms: -4 + 13x = 12x + -6 Reorder the terms: -4 + 13x = -6 + 12x Solving -4 + 13x = -6 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -4 + 13x + -12x = -6 + 12x + -12x Combine like terms: 13x + -12x = 1x -4 + 1x = -6 + 12x + -12x Combine like terms: 12x + -12x = 0 -4 + 1x = -6 + 0 -4 + 1x = -6 Add '4' to each side of the equation. -4 + 4 + 1x = -6 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = -6 + 4 1x = -6 + 4 Combine like terms: -6 + 4 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| 5x+1=2.2 | | 112-15=b | | 13x-7=5x-47 | | 12x+10=5x+24 | | 3x-12=9x-72 | | 9x+4=5.8 | | S/6-12=-16 | | 2+r=5 | | 3.3x+5.7y-6.7=0 | | 4x-11=10x-11 | | 4.25x+3=-3x^2 | | 3x+5=10x-30 | | (3.5x)+x=100 | | √8/21 | | 13x-9=8x-34A-5B-4C-2D-7E-1 | | 7x-11=8x-14 | | X-18y=45 | | F(xy)=2x^2+3xy+4y^2-5x+2y | | 4x+7=12x-33 | | 5x+12=4x+12 | | -2=-.6(4/x) | | 7x-2/3=3 | | -2=-0.6(4/x) | | 9x+12=4x+62 | | 7n^2+9=-123 | | 2y=43-17 | | 4x+9=5x+6 | | 6(x)-y=9 | | -4x^2+6=2x | | 14x+12=3x+78 | | 2y=43-7 | | 4x+9=7+5x |